How to engage and attract virtual influencers' followers: a new non-human approach in the age of influencer marketing - Melnychuk, Hanna-Anastasiia; Arasli, Huseyin; Nevzat, Raziye (Emerald Group Publishing Ltd, 2024)
PurposeThe purpose of this study is to identify the process of virtual influencer stickiness in the age of influencer marketing, which has received little attention in the literature. This is essential because the research creates a theoretical model of follower loyalty/stickiness to virtual influencer techniques from the standpoint of influencer marketing, which has a substantial effect on the evolution of the global marketing world.Design/methodology/approachIn 2022, 302 people who currently follow an Instafamous virtual influencer took part in an Instagram self-administered online survey.FindingsThe findings show that both expertise and trustworthiness have a positive and significant influence on parasocial interaction, which in turn has a significant influence on virtual engagement and stickiness.Originality/valueThis research will specifically assist international readers in understanding how to harness and increase the efficiency and efficacy of interactive marketing strategies and methods to engage and retain followers of Instafamous virtual influencer. Moreover, the findings will be beneficial to opinion leaders, brand managers, company investors, entrepreneurs and service designers.HighlightsThe study pioneers a holistic virtual follower stickiness mechanism that comprises the role of source credibility, parasocial interaction, informational influence and virtual follower's engagement and their interrelationship to each other.This study is based on parasocial interaction theory and source credibility theory to understand the relationship between virtual followers and influencers stickiness process at social media platforms.In addition, the study examined the subsequent effects of sources of credibility components on parasocial interaction; as well as, on virtual follower engagement and stickiness.This study also categorized and examined the moderating effects exerted by the genres of informative influence of virtual influencer.
Keywords: Virtual follower stickiness; Virtual follower engagement; Parasocial interaction; Source credibility; Informational influence; Instagram